Analisis Stabilitas Artificial Reefs Tipe Hexagonal - Muhammad Rifqi Hanif; Haryo Dwito Armono (Rekayasa, 2022)
In solving the problem of abrasion and also protecting marine ecosystems, it is necessary to come up with an idea, namely a wave energy retaining structure that is also capable of being a habitat for marine biota. Therefore, in this study, artificial coral reefs were tested which are considered capable to solve these problems, plus those which at the same time rehabilitate damaged coral reef ecosystems. The artificial reefs model in this test is a hexagonal type with one layer arrangement. To get the success value (KD) of artificial reefs, it is seen from the percentage of damage caused by the influence of height and wave period. Then the KD value was calculated using the Hudson formula so that it was found that the hexagonal type artificial reefs had a KD value = 1.2.